Tractarians and the "condition of England" the social and political thought of the Oxford movement - Skinner, S. A. (Simon Andrew) (Oxford historical monographs., 2004)
Making use of neglected periodical and fictional material, Simon Skinner challenges the construction of tractarianism as an episode in church history, and the convention that tractarians had little interest in social questions.